NEGATIVE EFFECTS OF PARASITIC HELMINTHS ON THE HUMAN BODY AND MEASURES TO PREVENT HELMINTHS FROM ENTERING THE HUMAN BODY (Лучшие интеллектуальные исследования, 2025)
Abstract:Worms it is a parasite worms considered animals , plants _ and basically to people parasitism by doing lives and develops and increases . Ours in our country More than 60 worms type have. To statistics according to , land of the planet out of every 3 people one worms-parasites by affected.